2011
DOI: 10.1111/j.1749-6632.2010.05852.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitization of tumors by resveratrol

Abstract: Because tumors develop resistance to chemotherapeutic agents, the cancer research community continues to search for effective chemosensitizers. One promising possibility is to use dietary agents that sensitize tumors to the chemotherapeutics. In this review, we discuss that the use of resveratrol can sensitize tumor cells to chemotherapeutic agents. The tumors shown to be sensitized by resveratrol include lung carcinoma, acute myeloid leukemia, promyelocytic leukemia, multiple myeloma, prostate cancer, oral ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
189
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(195 citation statements)
references
References 62 publications
3
189
1
2
Order By: Relevance
“…However, the mechanisms regulating the suppressive signaling of resveratrol on IL-1␤-induced NF-B transcriptional activity have not yet been fully understood. Opposite to this, several lines of evidence have also reported that resveratrol induces apoptotic cell death in several tumor cell lines through the stimulation of caspase-3, accumulation of p53 and p21, and cleavage of poly-(ADP-ribose) polymerase (51,59,60). There may be different and multiple reasons for these diverse findings.…”
Section: Discussionmentioning
confidence: 85%
“…However, the mechanisms regulating the suppressive signaling of resveratrol on IL-1␤-induced NF-B transcriptional activity have not yet been fully understood. Opposite to this, several lines of evidence have also reported that resveratrol induces apoptotic cell death in several tumor cell lines through the stimulation of caspase-3, accumulation of p53 and p21, and cleavage of poly-(ADP-ribose) polymerase (51,59,60). There may be different and multiple reasons for these diverse findings.…”
Section: Discussionmentioning
confidence: 85%
“…Resveratrol has shown much promise in treating cancer in laboratory animals and in vitro human cell studies [68][69][70], yet there is still a large void in human research. This may soon change, as six of the clinical trials currently listed for resveratrol on www.clinicaltrials.gov (Table 2 in Supporting Information) include cancer patients as a target population.…”
Section: Current Limitations To Human Clinical Trial Datamentioning
confidence: 99%
“…Resveratrol, a natural compound found in the skin of red grapes and a constituent of red wine, is believed to play a significant role in the reduction of cardiovascular events (Artaud-Wild et al 1993;Gupta et al 2011). Multiple studies have shown that resveratrol can activate sirtuin 1 (SIRT1), a histone deacetylase, and inhibit p300 (Howitz et al 2003;Gracia-Sancho et al 2010).…”
Section: Effect Of Other Natural Compounds On Epigeneticsmentioning
confidence: 99%